Dynamical Complexity and Numerical Bifurcation Analysis of a Reaction-Diffusion Predator-Prey System - Lajmiri, Z.; Orak, I.; Khoshsiar, R.; Azizi, P. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we consider a diffusive predator-prey system with modified Holling-Tanner functional response under homogeneous Neumann boundary condition . Dynamics of the system is very sensitive to the variation of the initial conditions. We determine stability and dynamical behaviors of the equilibrium of this system. The dynamical behaviors consist of Andronov-Hopf bifurcation, limit cycles and Bogdanov-Takens bifurcations. Numerical simulation results are given to support our theoretical results.